Model Desain Key Performance Indicators (KPI) Sustainable Supply Chain Management (SSCM) Pada Industri Tekstil Menggunakan Metode Analytical Hierarchy Process - Dewi Putri Mardiana; Rangga Primadasa (Jurnal Rekayasa Sistem Industri, 2023)
This paper aims to design Key Performance Indicators (KPI) to evaluate sustainable supply chain management (SSCM) in the textile industry in Indonesia. Supply chain sustainability has various challenges in supply chain management from an environmental, social and economic perspective. This encourages better performance management.The method used in identifying SSCM KPIs in the textile industry is carried out by surveys and field studies and validation of the respondent's questionnaire assessment, there are 20 SSM KPIs obtained during direct research in one of the textile industries in Kudus City. Precision performance is obtained by assessing the level of importance between KPI indicators measured using the Analytical Hierarchy Process (AHP) method. According to respondents' preferences, the most dominant indicators are economic indicators, followed by environmental indicators and then social indicators. The results of these KPIs are used to measure the performance of SSCM in the textile industry and as a reference for recommendations for performance improvement.